The effect of Cinnamon on primary dysmenorrhea: A randomized, double-blind clinical trial. (November 2018) - Jahangirifar, Maryam; Taebi, Mahboubeh; Dolatian, Mahrokh
Abstract: Background: Primary dysmenorrhea is a cyclic cramp in pelvic which interferes with daily activity. This study determined the effect of Cinnamon on relieving dysmenorrhea. Methods: This is a randomized, double-blind clinical trial. The intervention group received Cinnamon (capsules contained 1000 mg cinnamon) and the control group received placebo (capsules contained 1000 mg starch) during the first 72 h of menstruation for two cycles continuously. The Visual Analogue Scale was used to determine the severity of pain. The subjects were followed up for two cycles. Descriptive statistics, Independent T test, analysis of variance (ANOVA) with repeated measures were used for continuous quantitative variables. Mann-Whitney and Chi-square tests were used for nominal and ordinal qualitative variables. Results: The results showed the mean intensity of dysmenorrhea significantly decreased over time in both groups (time: P < 0.001) and this reduction was significantly different over time between two groups (time*group: P = 0.02). There is significantly more reduction in the intervention group. Also the pain reduction in the intervention group was significantly lower than the placebo group after the first treatment (P = 0.001) and the second treatment (P = 0.002) compared to before treatment. Conclusions: Cinnamon can reduce the intensity of primary dysmenorrhea. This aromatic spice for relive of primary dysmenorrhea is recommended.